COMPARATIVE ANALYSIS OF THE REDUCTION OF SUSPENDED SOLIDS USING Opuntia ficus indica AND FERRIC CHLORIDE IN THE WATERS OF THE LURIN RIVER - Tito, Anderson Manrique; Ruiz, Carmen; Rodriguez, Ciro; Aquije, Carmen; Bringas, Jorge; Esenarro, Doris (The journal of contemporary issues in business and government, 2021)
One of the world's significant concerns lately is the quality of water and its availability over time. Being one of the most critical basic needs for humanity, its care is elementary for the world. In this research, we develop mechanisms for its treatment, the process of coagulation, and flocculation, where synthetic coagulants are added to accelerate the settling of suspended solids. This process was divided into four parts for a better understanding. They are starting with the introduction that provides a broad overview of the research and describes the Lurín area's problem. The methodology indicates the experimental research design where the collected concentrations are measured, going through the two treatments' procedure (Opuntia ficus indica and Ferric Chloride) at different doses. The results present initial and final parameters with both coagulants' dose tests for determining periods and zones, showing parameters of treatment and removal of the coagulants concerning the Lurín river's water. Finally, the conclusions indicate that the natural coagulant Opuntia ficus Indica obtained the highest percentage of turbidity removal, removal of chemical oxygen demand, reduced biochemical oxygen demand, and generated lower costs than ferric chloride.